Towards the Artistry of Transcending Textual Conversion - Rafał Zygmunt (Language, Culture, Politics)
The present discussion, stressing the importance of interdependence between language and culture, somehow automatically directs our attention at the effective and expressive use of language, which is just the result of this sort of interrelationship. Undoubtedly, cultural competence combined with linguistic competence is responsible for expressiveness and thus, for success in communication.